A Framework to Measure Water and Energy Footprint at Demand Side - Maria Anityasari; Mar’atus Sholihah; Diesta Iva Maftuhah (Indonesian Journal of Life Cycle Assessment and Sustainability, 2017)
There is no doubt that water is an essential part of human life. Unfortunately it is often neglected and is not managed well. Flood and drought in many areas in Indonesia are examples of serious deficiency in water management. Urban areas, in particular, have serious threats in water sustainability due to the dramatic increase of population. Regrettably, there is little knowledge on water infrastructure in macro to micro level, people’s attitude toward water, stakeholders’ inter-connectivity in water management, institutional capabilities in managing water management, and appropriate technologies to use water wisely in different settings. At the demand side alone, complexities can be found in water usage infrastructure. A pilot survey found that more than 65% household in Surabaya installed water pump to access clean water. This means that the total environmental impact of water usage has to incorporate energy footprint in the equation, in addition to the water footprint itself. This paper will present a developed framework to portray the tangle between water and energy at the demand side and how to measure its environmental impact. Benefits of its implementation and potential future work will be discussed and outlined.